Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Dong, Wu-Shan; Liu, Peng-Fei; Liu, Yu; Du, Yu; Bi, Yan-Hui; Zhou, Zhi-Gang (Frontiers in Marine Science, 2020)
Nuf2p, a centromere-associated protein, is an indispensable component of Ndc80 complex which is important for stable microtubule-kinetochore attachment, chromosome pairing and spindle assembly in mitosis. Based upon contig sequences coding for Nuf2p from a pyrosequencing transcriptome of Saccharina japonica, primers were designed for molecular cloning of this kinetochore protein. The open reading frame (ORF) of this gene SjNuf2 was 1,452 bp long, encoding a putative protein consisting of 483 amino acids. Multi-sequence alignment showed SjNuf2p possessed several conserved domains of Nuf2, Spc7, SPT2 and MIT. To illustrate the location of SjNuf2p using immunocytochemistry, its ORF was inserted into a prokaryotic expression vector pET-28a. Then the recombinant SjNuf2p (rSjNuf2p) was induced to be expressed in Escherichia coli. The rSjNuf2p was verified by Western blotting with the commercial anti-6His-tag antibody and then purified using affinity chromatography. The polyclonal antibody of anti-SjNuf2p was raised against the purified rSjNuf2p. Western blotting with this prepared antibody showed the presence of SjNuf2p in the gametophytes of a Saccharina cultivar. SjNuf2p and alpha/beta-tubulin were subsequently co-localized to the paraffin sections of kelp chromosomes with their corresponding antibodies, thus illustrating that SjNuf2p could reside at the kelp centromeres. This study laid a solid foundation for kelp centromere and karyotype analyses.